Financing Large-Scale Mitigation by Smallholder Farmers: What Roles for Public Climate Finance? - Odhong', Charles; Wilkes, Andreas; van Dijk, Suzanne; Vorlaufer, Miriam; Ndonga, Samuel; Sing'ora, Brian; Kenyanito, Lucy (Frontiers in Sustainable Food Systems, 2019)
There is increasing interest in accessing climate finance to support low-emission, climate resilient agricultural development, but little is understood about how climate finance can be deployed to catalyze large-scale adoption of mitigation practices by smallholder farmers. This study assesses the potential roles of public climate finance in enabling smallholder farmers in Kenya's dairy sector to adopt low-emission farming practices. Drawing on multiple studies conducted as part of the design of a nationally appropriate mitigation action for the Kenyan dairy sector, it examines financing needs, institutional arrangements for channeling climate finance, and appropriate financial instruments. The study finds that financially profitable investments can be made by dairy farmers, but credit financing on commercial terms is not viable for dairy farmers lacking off-farm income sources. Dairy farmers make little use of formal financial institutions for several reasons, and while financial institutions have a strong interest in increasing their finance to the dairy sector, they face a variety of capacity constraints. Climate finance may have roles to play in strengthening linkages between dairy farmers and financial institutions, building capacities of different actors in the dairy and finance sectors, and enabling both farmers and financial institutions to manage risks. Concessional loans, credit guarantee funds and grants are all relevant financial instruments. If agriculture is to attract climate finance in support of large-scale mitigation action, a diversified, demand-responsive approach to financial innovation is required that engages different types of financial institution to support access to both savings and credit services tailored to the varied needs of men and women dairy farmers and the dairy value chain actors they work with.